Comparison of the financial cycle in advanced and emerging economies - Monteiro, Ornella Lassalette; Klosová, Anna, 1942-; Cabelo, Andrea; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
This dissertation argues that financial cycles are different for advanced economies and emerging countries. The main underlying reason is the different financial development that makes for instability in emeging markets which is pronounced by more intensive and amplified financial cycle. As such, even the policy implications are different.
Vedoucí práce: Anna Klosová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: economics of globalisation and european integration [obor dipl. práce]; diplomové práce; master's theses